Ligamen periodontal sebagai pendukung gaya kunyah Periodontal ligament acts to support mastication force - Rachman Ardan; Ine Suhartina; Rasmi Rikmasari; Gantini Subrata; Erna Kurnikasari; Deddy Firman (DiscoverSys Inc., 2011)
Support for removable partial denture (RPD) can be obtained from bone supported mucosa and or from periodontalligament of tooth. Support can also be obtained from implant. Tooth support (periodontal ligament) is better thanmucosal support because histologically, anatomically, and also physiologically, in addition, periodontal ligamentacts to resist mastication force